2016
DOI: 10.5830/cvja-2015-053
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cardiac structure and function in a modified rat model of myocardial hypertrophy

Abstract: SummaryAimIn this study we designed a modified method of abdominal aortic constriction (AAC) in order to establish a stable animal model of left ventricular hypertrophy (LVH). We also evaluated cardiac structure and function in rats with myocardial hypertrophy using echocardiography, and provide a theory and experimental basis for the application of drug interventions using the LVH animal model. We hope this model will provide insight into novel clinical therapies for LVH.MethodsThe abdominal aorta of male Wis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Brain natriuretic peptide is a particular cardiac neurohormone that rises in response to myocardial hypertrophy and dilatation (Dai et al 2016). BNP, sometimes referred to as B-type NPs and a part of the natriuretic peptide (NP) system, is primarily released by cardiomyocytes in response to cardiac stretch and ischemia and is crucial for the function of the cardiorenal system (Okamoto et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Brain natriuretic peptide is a particular cardiac neurohormone that rises in response to myocardial hypertrophy and dilatation (Dai et al 2016). BNP, sometimes referred to as B-type NPs and a part of the natriuretic peptide (NP) system, is primarily released by cardiomyocytes in response to cardiac stretch and ischemia and is crucial for the function of the cardiorenal system (Okamoto et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Most of them used an induction duration of more than 6 weeks, while a few focused on the early stage of cardiac hypertrophy. According to Wenjun Dai's work, 20 we used rats weighing 80–120 g to make up a 4‐week AAC‐induced cardiac hypertrophic model, which are younger rats rather than adults. Our data also showed that 4‐week induction by AAC showed significantly impaired cardiac function, increased heart size and cardiomyocyte size, and increased cardiac hypertrophic biomarkers Anp and b‐Mhc.…”
Section: Discussionmentioning
confidence: 99%
“…The abdominal aorta was occluded at the suprarenal level using a 2‐0 silk suture over a blunt 24‐G needle (the external diameter was 0.55 mm). 20 Rats were anaesthetised using 2% isoflurane (R510‐22‐16, RWD Life Science) and oxygen with a flow rate of 0.5 L/min and maintained with 1.5% isoflurane with an airflow of 0.3 L/min in an induction chamber connected with an animal anaesthesia machine. The sham groups ( n = 8) underwent similar surgery without placement of the aortic band.…”
Section: Methodsmentioning
confidence: 99%
“…The heart was removed, weighed, and then cardiac dimensions were measured. For each animal, the cardiac index was calculated by dividing the weight of the heart by the body weight [43]. Also, samples of brain tissue, the left ventricle, and the renal cortex were collected.…”
Section: Experimental Designmentioning
confidence: 99%